Genetics of aluminum tolerance in hexaploid oats - Federizzi, Luiz Carlos; Oliveira, Paulo Henrique; Nava, Itamar Cristiano (MTT, 2004)
Most of the sub-tropical and tropical regions of Brazil have soils with high levels of toxic aluminum (Al3+), reducing the yield of the non-tolerant crops. Tolerant cultivars are able to develop a healthy root system under aluminum toxic conditions; therefore it is important to identify sources of tolerance and understand its inheritance. The objective of this paper is to report the results obtained from several genetic studies involving tolerant and susceptible oat genotypes. Identification of susceptible and tolerant genotypes was based on the length of root regrowth in nutritive solution (Polle et al., 1978) after exposure to 20 ppm of aluminum (Sanchez-Chacon et al., 2000). Generations F2 to F6 from crosses between susceptible and tolerant genotypes were analyzed in the lab. The susceptible genotypes had very poor root regrowth (zero to 5mm) and the tolerant ones had more than 10mm. Tolerance to aluminum toxicity in the soil in Avena sativa is due to a single gene with dominance for tolerance. Studies from several different crosses demonstrated that there are at least two different alleles for tolerance. High levels of aluminum tolerance was found in many oat genotypes but the most important sources are UFRGS 17 and UPF 91Al100-1-4. Polle, C.R., et al. 1978. Crop Science 18: 823-827; Sanchez-Chacon et al. 2000. Pesquisa Agropecuária Brasileira 35: 1797-1808 (http://www.sct.embrapa.br/pab/uspab.asp).
Keywords: Ka; aluminum tolerance; hexaploid oats; Avena sativa; inheritance